WORK DISCIPLINE EFFECT ON EMPLOYEE PERFORMANCE AT THE ARTHA MITRA ABADI JAYA SAVINGS AND LOAN COOPERATIVE, MAGELANG CITY - Salsabila Alfi Luthfia Putri; Dian Marlina Verawati (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
The purpose of this study is to ascertain the effect that workplace discipline has on the staff at KSP Artha Mitra Abadi Jaya Magelang City. The population and sample for this study, which includes all 30 employees of KSP Artha Mitra Abadi Jaya Magelang City, were selected using quantitative methods. Because every member of the population was sampled, saturated sampling was utilized in this investigation and employed a questionnaire that was provided to participants to gather data, which was then processed using the data analysis methodology, which included the t researchers test, basic linear regression analysis, and the classical assumption test. The study's findings indicate that KSP Artha Mitra Abadi Jaya Magelang City employees' performance is significantly influenced by work discipline.